Neuroinflammation and status epilepticus: a narrative review unraveling a complex interplay - Foiadelli, T.; Santangelo, A.; Costagliola, G.; Costa, E.; Scacciati, M.; Riva, A.; Volpedo, G.; Smaldone, M.; Bonuccelli, A.; Clemente, A. M.; Ferretti, A.; Savasta, S.; et al. (Frontiers in Pediatrics, 2023)
Status epilepticus (SE) is a medical emergency resulting from the failure of the mechanisms involved in seizure termination or from the initiation of pathways involved in abnormally prolonged seizures, potentially leading to long-term consequences, including neuronal death and impaired neuronal networks. It can eventually evolve to refractory status epilepticus (RSE), in which the administration of a benzodiazepine and another anti-seizure medications (ASMs) had been ineffective, and super-refractory status epilepticus (SRSE), which persists for more than 24 hours after the administration of general anesthesia. Several preclinical and clinical studies have shown that neuroinflammation can contribute to seizure onset and recurrence by increasing neuronal excitability. Notably, microglia and astrocytes can promote neuroinflammation and seizure susceptibility. In fact, inflammatory mediators released by glial cells might enhance neuronal excitation and cause drug resistance and seizure recurrence. Understanding the molecular mechanisms of neuroinflammation could be crucial for improving SE treatment, which is mainly addressed with benzodiazepines and eventually phenytoin, valproic acid, or levetiracetam. IL-1β signal blockade with Anakinra has shown promising results in avoiding seizure recurrence and generalization in inflammatory refractory epilepsy. Inhibiting the IL-1β converting enzyme (ICE)/caspase-1 is also being investigated as a possible target for managing drug-resistant epilepsies. Targeting the ATP-P2X7R signal, which activates the NLRP3 inflammasome and triggers inflammatory molecule release, is another avenue of research. Interestingly, astaxanthin has shown promise in attenuating neuroinflammation in SE by inhibiting the ATP-P2X7R signal. Furthermore, IL-6 blockade using tocilizumab has been effective in RSE and in reducing seizures in patients with febrile infection-related epilepsy syndrome (FIRES). Other potential approaches include the ketogenic diet, which may modulate pro-inflammatory cytokine production, and the use of cannabidiol (CBD), which has demonstrated antiepileptic, neuroprotective, and anti-inflammatory properties, and targeting HMGB1-TLR4 axis. Clinical experience with anti-cytokine agents such as Anakinra and Tocilizumab in SE is currently limited, although promising. Nonetheless, Etanercept and Rituximab have shown efficacy only in specific etiologies of SE, such as autoimmune encephalitis. Overall, targeting inflammatory pathways and cytokines shows potential as an innovative therapeutic option for drug-resistant epilepsies and SE, providing the chance of directly addressing its underlying mechanisms, rather than solely focusing on symptom control.